Effects of FMO3 Polymorphisms on Pharmacokinetics of Sulindac in Chinese Healthy Male Volunteers. (26th February 2017) - Tang, Yong-Jun; Hu, Kai; Huang, Wei-Hua; Wang, Chong-Zhi; Liu, Zhi; Chen, Yao; Ouyang, Dong-Sheng; Tan, Zhi-Rong; Zhou, Hong-Hao; Yuan, Chun-Su
Abstract : Sulindac is a nonsteroidal anti-inflammatory drug, which is clinically used for the ailments of various inflammations. This study investigated the allele frequencies of FMO3 E158K and E308G and evaluated the influences of these two genetic polymorphisms on the pharmacokinetics of sulindac and its metabolites in Chinese healthy male volunteers. Eight FMO3 wild-type (FMO3 HHDD ) subjects and seven FMO3 homozygotes E158K and E308G mutant (FMO3 hhdd ) subjects were recruited from 247 healthy male volunteers genotyped by PCR-RFLP method. The plasma concentrations of sulindac, sulindac sulfide, and sulindac sulfone were determined by UPLC, while the pharmacokinetic parameters of the two different FMO3 genotypes were compared with each other. The frequencies of FMO3 E158K and E308G were 20.3% and 20.1%, respectively, which were in line with Hardy-Weinberg equilibrium (D ′ = 0.977, r 2 = 0.944). The mean values of C m a x, A U C 0 – 24, and A U C 0 – ∞ of sulindac were significantly higher in FMO3 hhdd group than those of FMO3 HHDD group (P < 0.05 ), while the pharmacokinetic parameters except T m a x of sulindac sulfide and sulindac sulfone showed no statistical difference between the two groups. The two FMO3 mutants were in close linkage disequilibrium and might play an important role in the pharmacokinetics of sulindac in Chinese healthy male volunteers.